A multimodal intervention to improve hand hygiene in ICUs in Buenos Aires, Argentina: a stepped wedge trial - Rodriguez, Viviana (2015)
Issue: Hand hygiene is a cost-effective measure to reduce microbial transmission (Teare EL, Cookson B, French GL, et al. UK handwashing initiative. J Hosp Infect. 1999;43:1–3.) and is considered to be the most important measure to prevent healthcare-associated infections (Pittet D, Allegranzi B, Sax H, Evidence-based model for hand transmission during patient care and the role of improved practices. Lancet Infect Dis 2006;6:641–52). Unfortunately, the compliance rate of healthcare workers (HCWs) with recommended hand hygiene procedures is less than expected. Initial assessment: In order to estimate the effect of a multimodal intervention on improving healthcare workers’ compliance with hand hygiene in eleven intensive care units (ICUs) from 11 hospitals of Buenos Aires, a randomized cluster-stepped wedge trial was designed. Choice of solution and implementation: A multimodal intervention was designed based on practices characterized by being evidence-based, low cost and suggested by qualitative research: (i) leadership commitment, (ii) surveillance of materials needed to comply with hand hygiene and alcohol consumption, (iii) utilization of reminders, (iv) a storyboard of the project and (v) feedback (hand hygiene compliance rate). Evaluation: The study enrolled 705 participants, comprising nurses (66.4%), physicians (25.8%) and other HCW (7.8%) along 9 months of observation. Compliance with hand hygiene in the control group was 66.0% (2354/3565) vs. 75.6% (5190/6864) in the intervention group. Univariate analysis showed an association between the intervention and hand hygiene compliance (odds ratio, OR 1.17; 95% confidence interval (CI), 1.13–1.22). The effect was still present after adjustment by calendar’s time and providers’ characteristics-age, gender and profession (OR 1.08; 95% CI, 1.03–1.14). Lessons learned: His study supports that a multimodal intervention was effective to improve compliance with hand hygiene in ICUs.